DAMPAK FINANSIAL SERANGAN SIBER TERHADAP KINERJA KORPORASI: SCOPING REVIEW - Gunibala, Zakir Yusuf; Maharani, Satia Nur; Pujiningsih, Sri (Jurnal Daya Saing, 2025)
: Rapid digital development has improved the operational efficiency of companies, but also increased exposure to the risk of cyber-attacks that can have a financial impact. This study aims to map and analyze the literature addressing the financial impact of cyberattacks on companies across sectors through a scoping review approach. The review process was based on the framework of Arksey and O'Malley (2005), including five stages: identification of research questions, search for relevant literature, selection of articles, data mapping, and preparation and reporting of results. A total of 10 selected scientific articles were analyzed and grouped into four main themes: (1) financial impacts and costs and (2) financial market reactions to cyberattacks. The findings show that cyberattacks cause real financial losses, including reduced stock prices, recovery costs, and reputational damage. The impact varies depending on industry sector, security readiness level, and transparency of incident reporting. The study also found gaps in cost estimation methodologies and incident reporting limitations that make comparative assessments between studies difficult. Therefore, future research should develop a standardized cost estimation approach, expand the geographical context of the study, and examine the long-term impact of cyberattacks on the financial sustainability of companies.